From vulnerability to resilience: Examining the Sister Village program's approach to volcanic disaster risk reduction using the DROP model - Dina Ruslanjari; Retno Argian Pangesti Putri; Diana Puspitasari; Retnadi Heru Djatmiko; Ryo Tanaka; Hasri Alvionita Hasan; Taaj Nabil; Nabilla Auriel Fajarian (Progress in Disaster Science)
This study examines the implementation of the Sister Village Program in enhancing community-based disaster resilience in Umbulharjo Village, located in the eruption-prone zone of Merapi Volcano. Using the Disaster Resilience of Place (DROP) Model approach, this research evaluates the key elements that shape disaster resilience, including mitigation, preparedness, adaptive capacity, and inter-village collaboration. The DROP Model integrates various components that influence a region's ability to manage, respond to, and recover from disasters, covering ecological, social, economic, institutional, and community competence aspects. This approach provides a comprehensive overview of a region's resilience to disasters and offers practical guidance for improving community and regional resilience. The study highlights the importance of planned mitigation and preparedness, and active community participation in reducing disaster impacts and accelerating post-disaster recovery. The Sister Village Program which involves knowledge exchange, infrastructure improvement, and strengthening the adaptive capacity of both villages, serves as an effective disaster risk reduction model. The findings also show that collaboration between villages and institutions, along with the strengthening of social infrastructure, play a crucial role in enhancing disaster resilience. The results of this study identify that by integrating these elements, the Sister Village Program can create stronger and more sustainable long-term disaster resilience. This model aligns with the Sustainable Development Goals (SDGs), particularly those related to disaster risk reduction and community capacity building. Thus, the Sister Village Program in Umbulharjo Village demonstrates significant potential for building sustainable resilience through an inclusive and collaborative community-based approach.